1983
DOI: 10.1017/s0022172400060356
|View full text |Cite
|
Sign up to set email alerts
|

A serological evaluation of 1979–1982 Kenyan foot-and-mouth disease type SAT 2 viruses

Abstract: Serological evaluations of foot-and-mouth disease type SAT 2 viruses isolated in Kenya between 1979 and 1982 were performed using the two-dimensional microneutralization test. Nine field isolates of epizootiological significance were compared with four vaccine viruses. The results obtained identified Tan 5/68 as the most appropriate reference vaccine virus strain since it had the broadest serological spectrum. Potent Tan 5/68 vaccines would be expected to provide adequate protection against the contemporary SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Better antigenic relationships were obtained for the SAT1 viruses belonging to the same topotype of the reference viruses (with less than 16 % aa variation). In the past, the combination of SAT1/SAR/9/81 and SAT1/KNP/196/91 in a tetravalent vaccine, containing also a SAT2 and a SAT3 strain, were able to protect against SAT1 outbreaks in Southern Africa (Hunter, 1998 (Ndiritu et al, 1983). The poor antigenic coverage of existing vaccine strains against field strains call for urgent development of multiple regionspecific or topotype-specific vaccine strains.…”
Section: Discussionmentioning
confidence: 99%
“…Better antigenic relationships were obtained for the SAT1 viruses belonging to the same topotype of the reference viruses (with less than 16 % aa variation). In the past, the combination of SAT1/SAR/9/81 and SAT1/KNP/196/91 in a tetravalent vaccine, containing also a SAT2 and a SAT3 strain, were able to protect against SAT1 outbreaks in Southern Africa (Hunter, 1998 (Ndiritu et al, 1983). The poor antigenic coverage of existing vaccine strains against field strains call for urgent development of multiple regionspecific or topotype-specific vaccine strains.…”
Section: Discussionmentioning
confidence: 99%
“…the vaccine strain) (Rweyemamu et al, 1977). Serological comparisons of SAT 2 viruses from Kenya revealed that there is extensive antigenic variation in this country, where two of the six major SAT 2 virus clusters occur (Ndiritu et al, 1983). In a comparative study of the antigenic and genetic diversity within SAT 1 , it was shown that viruses from different topotypes, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In eastern Africa, FMD was first reported in cattle in 1932 [ 15 ] and since then, the marketability of livestock and animal products within, and outside, the region has been negatively affected [ 16 ]. The maintenance of FMDV in the region has been attributed to various factors including: the presence of numerous wildlife reservoirs [ 7 , 17 19 ], communal and pastoral grazing systems that enable contact between livestock and wildlife [ 20 ], poor diagnostic capacity in the region [ 9 ], emergence of new strains [ 21 23 ], transboundary animal movements and traditional cultural practices such as the exchange of live animals for dowry and gifts [ 24 , 25 ]. East African countries have tried to control the disease mainly by quarantine and post outbreak vaccination.…”
Section: Introductionmentioning
confidence: 99%